A novel dual phase membrane 40 wt% Nd0.6Sr0.4CoO3−δ–60 wt% Ce0.9Nd0.1O2−δ: design, synthesis and properties. Issue 1 (9th November 2017) - He, Yuan; Shi, Lei; Wu, Fan; Xie, Weiwei; Wang, Shu; Yan, Dong; Liu, Peijiang; Li, Man-Rong; Caro, Jürgen; Luo, Huixia
Abstract : Oxygen permeation, stability and chemical bonding characteristics of 40 wt% Nd0.6 Sr0.4 CoO3− δ –60 wt% Ce0.9 Nd0.1 O2− δ (40NSCO–60CNO) dual-phase composite membrane reactors were investigated. Abstract : Oxygen permeation, stability and chemical bonding characteristics of 40 wt% Nd0.6 Sr0.4 CoO3− δ –60 wt% Ce0.9 Nd0.1 O2− δ (40NSCO–60CNO) dual-phase composite membrane reactors were investigated. The 40NSCO–60CNO oxygen permeable membrane was prepared via an in situ one-pot one-step EDTA–citric acid method. The crystal structure of the 40NSCO–60CNO dual phase material was characterized by X-ray diffraction (XRD) and in situ XRD. The microstructure was investigated using transmission electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM) combined with energy-dispersive X-ray spectroscopy (EDXS) and electron energy-loss spectroscopy (EELS). The results show that the 40NSCO–60CNO composite represents a micro-scale mixture of only the two pure phases NSCO and CNO. The oxygen permeation fluxes through the 40NSCO–60CNO dual phase membrane were measured at elevated temperatures (900–1000 °C) with one side of it exposed to synthetic air and the other side to a flowing He gas stream. A stable oxygen permeation rate of 0.90 mL cm −2 min −1 was obtained with a 0.4 mm thick membrane under an air/He oxygen partial pressure gradient at 1000 °C. The 40NSCO–60CNO dual phase membrane with a thickness of 0.6 mm showed a stable oxygen flux of 0.55 mL cm −2 min −1 at 950 °C for 100 h under pure CO2 sweeping.